Strategic Development of SMEs for Local Economic Sustainability Using the Quantitative Strategic Planning Matrix - Aslam Jumain (Department of Economics Education, Faculty of Economics, Universitas Negeri Makassar, 2025)
Small and medium enterprises (SMEs) play a crucial role in sustaining local economies by generating employment, fostering innovation, and strengthening community resilience. However, their strategic development often lacks structured, data-informed approaches that integrate competitiveness and sustainability. This study develops a hybrid analytical framework combining the SWOT–TOWS Matrix, the Internal–External (IE) Matrix, and the Quantitative Strategic Planning Matrix (QSPM) to identify and prioritize strategic alternatives for sustainable enterprise growth. Using SMES Tompobulu, a coffee-processing business in South Sulawesi, Indonesia, as a case study, the research evaluates internal strengths and weaknesses alongside external opportunities and threats to determine the most effective strategic direction. The analysis positions the enterprise in the Grow and Build quadrant of the IE Matrix (Internal Factor Evaluation = 3.05; External Factor Evaluation = 2.80), indicating a strong internal capacity and moderately favorable external environment. Among two alternative strategies, direct export expansion achieved a higher Total Attractiveness Score (2.94) compared to local market penetration (2.64). The findings demonstrate that integrating classical strategic tools with sustainability criteria enhances decision accuracy, competitiveness, and long-term resilience. This study contributes methodologically by adapting QSPM for sustainability-oriented strategy evaluation and empirically by illustrating how SMEs can align export readiness, innovation, and environmental stewardship to achieve sustainable competitiveness. The framework offers practical implications for policymakers and enterprise support institutions to design place-sensitive interventions that reinforce SMEs transformation and inclusive local growth.